7 - Quand le Football Burundais devient un Enjeu Identitaire et Politique - Mvutsebanka Celestin; Salvator Nahimana (African Sociological Review, 2020)
The purpose of this article is to demonstrate the link that football has with politics in Burundi, a country that is undermined by ethnicity. This study shows how football is used in socio-identity dynamics to reduce tensions between two rival ethnic groups, thus strengthening the legitimacy of the political power in place. Football in Burundi is captured at the crossroads of the sociology of sport and political sociology during which it is used to the detriment of the formation of collective identities and social cohesion. Football is used to lower tensions between two divided ethnic groups (Hutu, Tutsi) and allow to lower their differences to communicate in the common jubilation of local meetings organized on purpose on the one hand and in the consecration of the national team in international meetings on the other hand. The article thus contributes to fuel reflections on the challenges of football in the development of collective, even national, identities, while highlighting its instrumentalization vis-à-vis politics for the purposes of social cohesion.